A seven‐year study on the effects of four tillage modes on soil physicochemical properties, microbial biomass, enzymatic activities, and grain yield in a rice–ratoon rice cropping system. Issue 2 (11th January 2023) - Jiang, Shuochen; Du, Bin; Hu, Fengqin; Zhang, Haiwei; Kong, Pan; Wu, Qixia; Zhu, Jianqiang
Abstract: Ratoon rice is resource efficient to produce economically sound and environmentally sustainable rice production. However, there is no more information on the relative impact of soil tillage practices on soil physical and chemical properties, microbial biomass, and enzymatic activity, and grain yield in a rice–ratoon rice cropping system remains to be tested. Systematic study of soil under ratooning rice model is a problem to be solved in the development of ratooning rice model. This study primarily investigated the long‐term (from 2014 to 2020) changes in soil bulk density (BD), soil organic carbon (SOC) concentration, total nitrogen (TN) concentration, microbial biomass, β‐glucosidase activity (BG), urease activity (UR), and yield under four treatments: no‐tillage (NT), no plowing tillage + rotatory tillage (RT), plowing tillage in winter + rotatory tillage (PTW), and plowing tillage in spring + rotatory tillage (PTS). NT increased BD by 9.65%–12.97%, and RT increased the 20–40 cm soil layer BD by 8.80% in 2020, compared with the baseline initial value (in 2014). Plowing tillage (PT) time had no significant effect on BD. All tillage methods decreased the SOC concentration in the 0–20 cm soil layer, and only RT increased the TN concentration. PT was the only treatment that increased the SOC and TN concentrations in the 20–40 cm soil layer. Both the main‐season rice yield and the ratoon season rice yield ranked PTW > PTS > NT > RT, in which the main‐season rice yield increased by 28.15% and the ratoon season rice yield increased by 25.19% in PTW. Overall, the PTW treatment had the highest microbial biomass, enzyme activity, and grain yield compared with the other tillage methods. In conclusion, plowing tillage in winter + rotatory tillage is a more suitable tillage method under the mode of ratooning rice. Abstract : A long‐term study on the effects of tillage on soil traits and yield in a rice–ratoon rice cropping system has been carried out. Plowing tillage in winter + rotatory tillage (PTW) maintains soil permeability at a depth of 0–40 cm. Independent of tillage methods and ratoon rice systems require increased SOM input to maintain C storage. PTW had the highest soil microbial biomass, soil enzyme activity, and grain yield.